Trigonometric Widths of the Nikol’skii–Besov Classes in the Lebesgue Space with Mixed Norm - Akishev, G. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We establish exact-order estimates for the trigonometric widths of the Nikol’skii–Besov classes of periodic functions of many variables in the Lebesgue space with mixed norm.